2016
DOI: 10.1021/acs.jpcb.5b10575
|View full text |Cite
|
Sign up to set email alerts
|

β-Hairpin Crowding Agents Affect α-Helix Stability in Crowded Environments

Abstract: The dense, heterogeneous cellular environment is known to affect protein stability. It is now recognized that attractive "quinary" interactions with other biomacromolecules in the cell, referred to as the crowding agents, play a significant role in determining the stability of the protein of interest or test protein. These attractive interactions can reduce or overcome the stabilizing effect of the excluded volume of the crowding agents. However, the roles of specific interactions, such as hydrogen bonding and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Pioneering simulations of this kind, based on molecular dynamics methods, have recently been reported. 8,[35][36][37][38] The present study focuses on crowder-induced changes in the equilibrium properties of our two peptides. The problem of determining folding/unfolding equilibria in the presence of the crowders is tackled by direct Monte Carlo-based simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering simulations of this kind, based on molecular dynamics methods, have recently been reported. 8,[35][36][37][38] The present study focuses on crowder-induced changes in the equilibrium properties of our two peptides. The problem of determining folding/unfolding equilibria in the presence of the crowders is tackled by direct Monte Carlo-based simulation.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of the native states of proteins immersed in a crowded macromolecular environment, such as that present in a living cell, can substantially differ from that in dilute conditions. Previous experiments and simulations showed that macromolecular crowding can lead to both stabilization and destabilization of the native fold. This variable outcome arises from an interplay of two phenomena, the stabilizing excluded volume effect and the potentially destabilizing effect of weak transient (quinary) interactions, and thus, it depends on the composition of the environment and on the amino acid sequence. ,,, …”
mentioning
confidence: 99%
“…97 A second theme is the modulation of secondary structure propensities as a result of crowder interactions. While this has been systematically analyzed using coarse-grained models, 95,96 atomistic simulations have provided evidence for an apparent stabilization of secondary structure elements, especially helices, as a result of crowding. 27,97,98,174 One way to understand that is via crowder amino acid side chain interactions that stabilize helices 95 or β-hairpin turns.…”
Section: Simulationsmentioning
confidence: 99%